The Relationship Between Gross Domestic Product with International Balance of Payment: Empirical Evidence from Indonesia - Syukri, Adya Utami (Universitas Airlangga, 2020)
This research aims to determine the relationship between gross domestic product, exports, imports, foreign exchange reserves, and foreign debt in Indonesia from 1978 – 2018. As a developed country, Indonesia must know the interrelatedness between the GDP and the variable in the international balance of payment to move the economy well. This research using the Vector Autoregression (VAR) method that includes ADF Test, Granger Causality, Johanssen Co-integration, Vector Error Correction Model (VECM), and forecasting with Impulse Response Function (IRF) and Variance Decomposition (VD). From the Granger causality test results that have been carried out among the five variables, it is concluded that there is no causality relationship, but there are six one-way relationships. Simultaneously, the cointegration test from the Johanssen Co-Integration test results in the five variables tested. Forecasting for the next ten years through the IRF and VD tests shows that GDP positively responds to foreign debt and exports. Exports provide a positive response to GDP and imports. Imports give a positive response to exports, GDP, and foreign exchange reserves. At the same time, foreign debt gives a positive reaction to GDP and imports. Then foreign exchange reserves provide a positive response to exports and foreign debt. The government needs to allocate funds from foreign debt to the export sectors to increase GDP. Keywords: Causality, VECM, Gross Domestic Product, Exports, Foreign Debt Java Industry JEL: F14, F41, C01